Predictors of employee well-being: A global measurements using reflective-formative model - Willy Tambunan; Sri Gunani Partiwi; Adithya Sudiarno (Heliyon)
Background: Employee well-being (EW) is an integral part of occupational safety & health. Therefore, measuring EW is very important for holistically evaluating well-being instruments and measurement models. This research aimed to identify and confirm dimensions that significantly contribute to EW and also to examine the reliability and validity of the formative model of EW. Methods: The survey consisted of 89 items from a well-being questionnaire administered to 426 employees in the coal mining industry, covering five domains. Measurements were analyzed using partial least squares–structural equation modelling (PLS-SEM) with SmartPLS 4.1.1. The measurement and analysis were conducted in two stages, the first of which used a reflective model. Subsequently, the results of the first stage were used in the second stage as a formative model to measure EW globally. Result and conclusion: Home, Community, and Society (HCS), Health Status (HS), Workplace Environment and Experience (WEE), Workplace Policies and Culture (WPC), as well as Workplace Environment and Safety Climate (WPE) domain significantly contributed to EW, as identified through first-order reflective and second-order formative models. Contribution: This research developed a measurement model for EW with two orders: first-order reflective and second-order formative. It also offered practical insights for organizations and companies to measure and understand EW, providing a basis for implementing effective interventions.